ChemInform Abstract: Angucyclines from an Insect‐Derived Actinobacterium Amycolatopsis sp. HCa1 and Their Cytotoxic Activity. Issue 16 (28th March 2013) - Guo, Zhi Kai; Liu, Shou Bai; Jiao, Rui Hua; Wang, Ting; Tan, Ren Xiang; Ge, Hui Ming
Abstract isolation, structural determination and cytotoxic activity of two new compounds, amycomycin A (I), and amycomycin B (II) along with five known compounds